Genetic structure of the population of Przewalski’s horse (Equus przewalskii) according to cytogenetic and ISSR markers - Lyubov Starodub; Mykola Porhun; Nataliya Mokhnachova; Andrii Berezovsky; Nataliya Yasinetska; Kyrylo Kopylov (Біологічні студії)
Background. Przewalski’s horse is included in the Red List of the International Union for Conservation of Nature and the Red Data Book of Ukraine as an endangered species. To confirm the uniqueness and consolidation of rare animal species, cytogenetic and molecular genetic monitoring is necessary. Obtaining biological material (blood) for genetic research is preceded by immobilization of wild ungulates. The successful selection of drugs for the purpose of sedation and analgesia helps to preserve the life and health of the animal. Materials and Methods. Przewalski’s wild horse population (10 heads) of the F. E. Falz-Fein “Askania-Nova” biosphere reserve, immobilization of animals with the Madison drug and the Reverson antidote, cytogenetic and molecular genetic (ISSR-fingerprinting) analysis. Results. The effectiveness indicators of doses of Madison and Reverson were: in horses m = 200 kg – a dose of Madison 20 mL/head, immobilization after 22 min, in horses m = 300 kg, a dose of Madison – 25 mL/head, immobilization in 20–22 min. The Reverson antidote was applied in the following doses: animal m = 200 kg – a dose of Reverson 5–15 mL/goal, cessation of the sedative effect – 12 min; animal m = 300 kg – a dose of Reverson 5–15 mL/goal, cessation of the sedative effect – 18 min. Observation of the effect of the drugs did not reveal any negative side effects. Cytogenetic analysis determined the karyotype norm of somatic cells with 2n = 66 chromosomes. Genomic disorders, aneuploidy, accounted for 6.7%, polyploidy – 1.3 %. Structural violations (chromosomal and chromatid breaks) were not detected. The results of the micronucleus test: the share of lymphocytes with a micronucleus – 3.0 ‰, binuclear lymphocytes – 2.3 ‰, mitotic index – 7.7 ‰. Genetic indicators of the population of Przewalski’s horses according to ISSR markers: when using (GA)9C as a primer, microsatellite repeats of polymorphic loci were not found, and according to primer (GAG)6C – 50 % of polymorphic loci. The main indicators of genetic diversity, with the help of ISSR markers: the share of polymorphic loci was 25 %, the average gene diversity per locus – 0.39, the Shannon–Wiener information index – 2.5. Conclusions. No negative side effects occur when Madison and Reverson drugs are used to immobilize Przewalski’s horses. According to the results of cytogenetic analysis, the stability of the karyotype of the studied animals was established. The study of genetic polymorphism of the horse population by ISSR markers (AG)9C and (GAG)6C indicates a high degree of genetic consolidation. All tested animals are relatively safe according to the revealed intra-population genetic diversity.